(untitled) (Revista Electrónica REDINE, 2018)
Genre-based teaching has widely been accepted worldwide in the context of English for Specific Purposes (ESP) in all its branches. However, Teachers do not have Access to systematic reviews providing input for an appropriate teaching practice according to the principles of Evidence Based Practice regarding Reading and reading comprehension teaching. Objective: to describe the effectiveness of genre-based teaching for reading comprehension in English for Specific Purposes students. Methodology: It was performed a systematic review. Search criteria included articles selection by skill (reading comprehension) and study design (experimental only), among other. Results: few studies on the efficiency of genre based teaching on Reading comprehension in English with Specific Purposes were found. Three categories arose: general effectiveness, foreign language proficiency and students’ gender. A trend to research on other variables was also observed. Conclusions: it is recommended to teach genre based reading comprehension in the teaching practice of English for Specific Purposes, taking into account groups’ homogeneity just in terms of general foreign language proficiency. However, more research on the issue is needed.